A thermosetting electrolyte-resistant adhesive and its preparation method and application

Through the use of thermoset electrolyte-resistant adhesive, the problems of burrs and metal particles in the welding connection of lithium batteries are solved, and the reliable bonding and high energy density of lithium battery electrodes and ears are achieved, which improves the safety and durability of the battery.

CN119752373APending Publication Date: 2025-04-04STEADYCHEM (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411958656.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the production process of traditional lithium batteries, burrs, welding slags, solder joints and metal particles generated when welding the electrode sheets and ears lead to an increase in internal resistance of the battery cell and short circuit, and the protective tape falls off or deforms under the erosion of the electrolyte, affecting the safety and energy density of the battery.

Method used

Thermoset electrolyte-resistant adhesive is used, which consists of alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler. By combining alicyclic epoxy resin and aliphatic epoxy resin, the combination of high-temperature rapid curing and low-temperature slow curing is achieved, forming a cured product with excellent thermal stability and solvent resistance.

Benefits of technology

Reliable bonding between lithium battery electrode sheet and electrode ear is achieved, and the bonding layer formed is resistant to electrolyte corrosion and is not easy to detach, avoiding burrs and metal particles during welding, and improving the safety and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217676400000191
    Figure BDA0005217676400000191
  • Figure BDA0005217676400000211
    Figure BDA0005217676400000211
Patent Text Reader

Abstract

The present application provides a thermosetting electrolyte-resistant adhesive and its preparation method and application, which belongs to the field of chemical materials. The thermosetting electrolyte-resistant adhesive provided in the present application is mainly made of alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler as raw materials; wherein, the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is (0.5‑5): 1. The thermosetting electrolyte-resistant adhesive provided in the present application can be used for the bonding of pole ears and pole pieces, can achieve rapid curing at high temperatures, and has good bonding properties and electrolyte resistance, to replace the existing welding technology, after the bonding is completed, there is no need to use tape to protect and preserve the active area on the back of the original welding position, thereby improving the safety and energy density of the battery without affecting the efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical materials, and in particular relates to a thermosetting electrolyte-resistant adhesive and a preparation method and application thereof. Background Art

[0002] In the traditional lithium battery production process, the pole pieces and tabs of lithium batteries are generally connected using welding processes such as ultrasonic welding or laser welding. Foreign matter such as burrs, welding slag, welding points and metal particles generated during the welding process will lead to an increase in the internal resistance of the battery cell and the occurrence of internal short circuits in the battery cell.

[0003] In this regard, in the prior art, after the electrode and the lug are welded, a protective tape is usually applied to the surface of the welding position to prevent burrs, welding slag and welding points from piercing the diaphragm, and to prevent metal particles from falling into the battery cell and causing safety problems. However, the protective tape is attached to the surface of the welding position, which is easily corroded by the electrolyte during the subsequent lithium battery processing and use, and automatically falls off or deforms, losing its protective effect; and the attachment of the protective tape will cover the active material layer on the electrode, reducing the energy density of the battery.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The present application provides a thermosetting electrolyte-resistant adhesive and a preparation method and application thereof, aiming to solve or alleviate at least one technical problem existing in the above-mentioned prior art.

[0006] The first aspect of the present application provides a thermosetting electrolyte-resistant adhesive, which is mainly made of alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler as raw materials; wherein the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is (0.5-5):1.

[0007] The present application designs the raw material components of the thermosetting electrolyte-resistant adhesive, and adopts alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler as the main raw materials; wherein, the compounding of alicyclic epoxy resin and aliphatic epoxy resin can give the thermosetting electrolyte-resistant adhesive bonding performance, and in the curing process of the thermosetting electrolyte-resistant adhesive, the alicyclic epoxy resin can be cured at high temperature (e.g., 180-250°C) before the aliphatic epoxy resin under the action of the curing agent because the epoxy group is directly connected to the alicyclic ring. It cures quickly under certain conditions to form a cured product with high cross-linking density and structural rigidity, which enables the cured product of the thermosetting electrolyte-resistant adhesive to have excellent thermal stability and solvent resistance. The aliphatic epoxy resin, under the action of the curing agent, can continue to cure slowly after the alicyclic epoxy resin has completely reacted, so as to synergize the toughening effect of the toughening agent and jointly alleviate the stress generated during the rapid curing of the alicyclic epoxy resin, thereby reducing the overall stress level of the cured product and ensuring the adhesion and reliability of the thermosetting electrolyte-resistant adhesive after curing.

[0008] In addition, the toughening agent can also cooperate with the alicyclic epoxy resin to enhance the solvent resistance of the cured product of the thermosetting electrolyte-resistant adhesive, so as to reduce the dissolution and swelling rate of the cured product in the electrolyte and further improve the bonding reliability; and the conductive filler can give the cured product of the thermosetting electrolyte-resistant adhesive conductive properties to meet the conductive requirements when connecting the lithium battery pole piece and the pole ear.

[0009] What is particularly critical is that the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is (0.5-5):1. Too high alicyclic epoxy resin mass ratio will inhibit the initial adhesion of the thermosetting electrolyte-resistant adhesive in the early stage of curing, and make the cross-linking density of the cured product too large, and the volume resistivity of the cured product too large; while too high aliphatic epoxy resin mass ratio will lead to weak electrolyte resistance of the cured product, poor adhesion and reliability; therefore, when the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is within the above range, the thermosetting electrolyte-resistant adhesive can have a high initial adhesion during the curing process, a low volume resistivity after curing, and strong solvent resistance, and the cured product can maintain excellent adhesion and reliability.

[0010] Therefore, the thermosetting electrolyte-resistant adhesive provided by the present application realizes the combination of high-temperature rapid curing and low-temperature slow curing of the thermosetting electrolyte-resistant adhesive through the synergistic combination of raw material components such as alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler. The cured thermosetting electrolyte-resistant adhesive not only has excellent solvent resistance and low dissolution and swelling rate, but also has excellent adhesion and reliability. The thermosetting electrolyte-resistant adhesive is applied to lithium batteries to achieve reliable bonding of pole pieces and pole ears. The bonding layer formed by it is resistant to electrolyte corrosion and is not easy to detach from the pole piece or the pole ear. It can replace the welding connection used when connecting the traditional pole piece and the pole ear, thereby avoiding the formation of burrs, welding slag, welding spots and metal particles during welding, and there is no need to use protective tape to cover the pole piece, which effectively improves the safety and energy density of the battery.

[0011] In some embodiments, the thermosetting electrolyte-resistant adhesive includes, by weight: 2-10 parts of alicyclic epoxy resin; 2-10 parts of aliphatic epoxy resin; 0.5-5 parts of toughening agent; 0.05-1 parts of curing agent; and 0.1-10 parts of conductive filler.

[0012] In some embodiments, the cycloaliphatic epoxy resin and / or the aliphatic epoxy resin is a liquid resin or a solid resin;

[0013] In some embodiments, when the alicyclic epoxy resin is a liquid resin, the liquid viscosity is 20-6000 cP;

[0014] In some embodiments, when the aliphatic epoxy resin is a liquid resin, the liquid viscosity is 50-100000 cP;

[0015] In some embodiments, the cycloaliphatic epoxy resin has an epoxide equivalent weight of 70-250 EEW (g / mol);

[0016] In some embodiments, the epoxy equivalent weight of the aliphatic epoxy resin is 90-500 EEW (g / mol);

[0017] In some embodiments, the functionality of the cycloaliphatic epoxy resin and / or the aliphatic epoxy resin is 2-4.

[0018] In some embodiments, the thermosetting electrolyte-resistant adhesive satisfies at least one of the following conditions AE:

[0019] A. Cycloaliphatic epoxy resins include 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether (3:1), 3,4-epoxycyclohexylmethyl methacrylate, vinylcyclohexene dioxide, 3,4-epoxycyclohexylmethyl at least one of 1,2-epoxy-4-vinylcyclohexane, tetrahydroindole diepoxide, 2-(3,4-epoxycyclohexyl)-5,5-spiro(3,4-epoxycyclohexyl)-1,3-dioxane homopolymer, (3,4,3',4'-diepoxy)bicyclohexane, 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylate) or dicyclopentadiene diepoxide;

[0020] B. aliphatic epoxy resins including at least one of bifunctional bisphenol A epoxy resins, bisphenol F epoxy resins, biphenyl epoxy resins, trifunctional aminophenol epoxy resins and naphthol epoxy resins;

[0021] C. The toughening agent includes at least one of polybutadiene rubber or nitrile rubber;

[0022] D. The curing agent is a cationic thermal curing agent, including at least one of hexafluoroantimonate, blocked diphenyliodonium antimonate, blocked diphenyliodonium phosphate, blocked triarylsulfonium hexafluorophosphate, ammonium blocked Lewis acid salt and pentafluorophenyl boric acid sulfonium salt;

[0023] E. The conductive filler includes at least one of superconducting carbon, graphite, hard carbon, silver powder, silver-coated copper powder, silver-coated nickel powder, nickel powder, silver-coated glass, silver-coated graphite, tin-silver-copper powder or carbon nanotubes.

[0024] In some embodiments, the toughening agent specifically includes at least one of epoxidized polybutadiene or core-shell rubber epoxy dispersion.

[0025] In some embodiments, the particle size of the conductive filler is in the range of 0.2-100 μm.

[0026] In some embodiments, the raw materials of the thermosetting electrolyte-resistant adhesive further include, by weight: a diluent: 0.01-5 parts; optionally, the diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent, or an oxidized cyclobutane diluent;

[0027] In some embodiments, the raw materials of the thermosetting electrolyte-resistant adhesive further include, by weight: 1-10 parts of epoxy-modified PP prepolymer; optionally, the molecular weight of the epoxy-modified PP prepolymer is 1000-100000.

[0028] The second aspect of the present application provides a method for preparing a thermosetting electrolyte-resistant adhesive, comprising uniformly mixing alicyclic epoxy resin, aliphatic epoxy resin, a curing agent, a toughening agent and a conductive filler in a predetermined proportion to obtain a thermosetting electrolyte-resistant adhesive.

[0029] In some embodiments, the preparation method specifically comprises the following steps:

[0030] The first mixing stage: uniformly mixing the alicyclic epoxy resin, the aliphatic epoxy resin and the toughening agent, or uniformly mixing the alicyclic epoxy resin, the aliphatic epoxy resin, the toughening agent and the epoxy-modified PP prepolymer to obtain a first mixed product;

[0031] The second mixing stage: adding the curing agent to the first mixed product and mixing evenly to obtain a second mixed product;

[0032] The third mixing stage: uniformly dispersing the conductive filler in the second mixed product to obtain a thermosetting electrolyte-resistant adhesive.

[0033] Furthermore, the third mixing stage also includes adding a predetermined proportion of diluent to the thermosetting electrolyte-resistant adhesive and mixing; optionally, dispersing the conductive filler in the second mixed product includes a first dispersion stage and a second dispersion stage performed in sequence; optionally, the first mixing stage, the second mixing stage and the third mixing stage are all performed under stirring conditions; optionally, in the first mixing stage or the second mixing stage: the stirring speed of the mixing container is controlled within the range of 5-60rpm, and the stirring time is controlled within the range of 10-30min; optionally, the stirring speed of the mixing container in the first dispersion stage is controlled within the range of 5-60rpm, and the stirring time is controlled within the range of 10-30min. The time is controlled within the range of 10-30min; optionally, the stirring speed of the mixing container in the second dispersion stage is controlled within the range of 30-100rpm, the dispersion speed of the mixing container is controlled within the range of 600-1000rpm, the stirring time is controlled within the range of 10-30min, and the mixing temperature is controlled below 30°C; optionally, adding a predetermined proportion of diluent to the thermosetting electrolyte-resistant adhesive includes a mixing stage and a vacuum degassing stage performed sequentially, and the stirring speed of the mixing container during the mixing stage and the vacuum degassing stage is controlled within the range of 5-60rpm, and the stirring time is controlled within the range of 10-30min.

[0034] The third aspect of the present application provides the thermosetting electrolyte-resistant adhesive as described above, and its use in bonding lithium battery pole pieces and tabs. DETAILED DESCRIPTION

[0035] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0036] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0038] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0039] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may also include or contain other components not listed, or may only include or contain the listed components.

[0040] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0041] Based on the foregoing, the general inventive concept of the embodiments of the present application is to provide a thermosetting electrolyte-resistant adhesive. Through the component design of the thermosetting electrolyte-resistant adhesive, the thermosetting electrolyte-resistant adhesive has excellent bonding properties, conductivity and electrolyte resistance after thermal curing. When applied to the lithium battery production process, the pole pieces and the pole ears can be directly bonded with the thermosetting electrolyte-resistant adhesive to replace the traditional technology of welding to connect the pole pieces and the pole ears, thereby avoiding the formation of burrs, welding slag, welding spots and metal particles during welding, and there is no need to use protective tape to cover the pole pieces, thereby effectively improving the safety and energy density of the battery.

[0042] Based on the above general inventive concept, an embodiment of the present application provides a thermosetting electrolyte-resistant adhesive, which is mainly made of alicyclic epoxy resin, aliphatic epoxy resin, a curing agent, a toughening agent and a conductive filler as raw materials; wherein the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is (0.5-5):1.

[0043] It can be understood that among the components of the thermosetting electrolyte-resistant adhesive, the compounding of alicyclic epoxy resin and aliphatic epoxy resin can make the cured product of the thermosetting electrolyte-resistant adhesive have adhesiveness, so as to facilitate the bonding of the pole piece and the pole ear; wherein, the epoxy group of the alicyclic epoxy resin is directly connected to the alicyclic ring, and under the action of the curing agent, it can achieve high-temperature rapid curing in the temperature range of 180 to 250°C, so as to complete the curing reaction before the aliphatic epoxy resin, and after curing, it has a large cross-linking density and a relatively small intermolecular gap to form a rigid structure, and the obtained cured product has a high glass transition temperature Tg (when used for the bonding of lithium battery pole pieces and pole ears, it is much higher than the aging temperature of 85°C for swelling and dissolution in the electrolyte), thereby promoting the thermosetting electrolyte-resistant adhesive to have a high initial strength during the curing process, and the cured product obtained by curing has good heat resistance, a high heat deformation temperature, a small curing shrinkage rate, a small swelling and dissolution rate, and can show strong solvent resistance even under the erosion of solvents such as electrolytes.

[0044] Since the cross-linking reaction speed of alicyclic epoxy resin is fast, large internal stress will be generated during the curing reaction. The stress release after curing will cause the adhesion of the cured product to decrease, that is, it will fall off by itself without external force when the external high and low temperature changes. Therefore, by compounding aliphatic epoxy resins in a predetermined ratio, the aliphatic epoxy resin has a slower curing speed than the alicyclic epoxy resin. After the alicyclic epoxy resin has a short curing reaction, it can continue to be post-cured at a lower heating temperature (such as 85-110°C) after the subsequent curing reaction is complete. The unreacted aliphatic epoxy resin is slowly cross-linked under the action of the curing agent, so as to cooperate with the toughening agent to alleviate the stress generated during the curing process of the alicyclic epoxy resin, so that the overall stress of the cured product is reduced, and finally the adhesion and reliability of the cured product are improved.

[0045] Furthermore, the toughening agent can increase the flexibility of the cured product, so as to cooperate with the alicyclic epoxy resin to improve the electrolyte resistance of the cured product. At the same time, it can also cooperate with the aliphatic epoxy resin to alleviate the stress generated during the curing process of the alicyclic epoxy resin, so as to reduce the overall stress level of the cured product formed by the thermosetting electrolyte-resistant adhesive and improve the adhesion and reliability of the cured product. In addition, the conductive filler can give the cured product formed by the thermosetting electrolyte-resistant adhesive conductivity to reduce the impact of the thermosetting electrolyte-resistant adhesive on the energy density of the lithium battery after being used for bonding the lithium battery pole piece and the pole ear.

[0046] It should be made clear that if the mass proportion of alicyclic epoxy resin is too high, the initial adhesion of the thermosetting electrolyte-resistant adhesive in the early stage of curing will be inhibited, the cross-linking density of the obtained cured product will be too large, and the volume resistivity of the cured product will be too large; and if the mass proportion of aliphatic epoxy resin is too high, the electrolyte resistance of the cured product will be weak, the peel strength of the cured product after soaking will be seriously reduced, and the adhesion and reliability will be poor; therefore, the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is designed to be (0.5-5): 1. Within this ratio range, alicyclic epoxy resin and aliphatic epoxy resin can give full play to their respective performance advantages, synergistically enhance the adhesion and reliability of the thermosetting electrolyte-resistant adhesive after curing, and ensure that the thermosetting electrolyte-resistant adhesive can have a high initial adhesion during the curing process, a low volume resistivity after curing, and strong solvent resistance.

[0047] In summary, through the synergistic effect of various components, the cured product of the thermosetting electrolyte-resistant adhesive can resist electrolyte erosion, maintain a low dissolution and swelling rate in electrolytes containing a variety of solvents, and has excellent adhesion and conductivity. It can be used in lithium batteries to achieve reliable bonding between pole pieces and tabs, replacing the welding connection used in traditional pole piece and tab connection, and there is no need to use protective tape to cover the active material layer on the pole piece, which effectively improves the safety and energy density of the battery.

[0048] It should be noted that the mass ratio of the alicyclic epoxy resin to the aliphatic epoxy resin is (0.5-5):1. For example, the mass ratio of the alicyclic epoxy resin to the aliphatic epoxy resin can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 0.5:1, 0.5:1, 0.5:1, 0.5:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5:1 or any mass ratio in the range of (0.5-5):1.

[0049] In some embodiments, the components of the thermosetting electrolyte-resistant adhesive include, by weight, 2-10 parts of alicyclic epoxy resin; 2-10 parts of aliphatic epoxy resin; 0.5-5 parts of toughening agent; 0.05-1 part of curing agent; and 0.1-10 parts of conductive filler. For example, by weight, the alicyclic epoxy resin in the thermosetting electrolyte-resistant adhesive may be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 6 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 64 parts, 66 parts, 67 parts, 68 parts, 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts The aliphatic epoxy resin can be 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or any parts by weight in the range of 2-10 parts; the toughening agent can be 0.5 parts, 1 The curing agent can be 0.05 part, 0.1 part, 0.15 part, 0.2 part, 0.25 part, 0.3 part, 0.35 part, 0.4 part, 0.45 part, 0.5 part, 0.55 part, 0.6 part, 0.65 part, 0.7 part, 0.75 part, 0.8 part, 0.85 part, 0.9 part, 0.95 part, 1 part or any weight part in the range of 0.05-1 part; the conductive filler can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or any weight part in the range of 0.1-10 parts.

[0050] It should be noted that, when the mass ratio of the alicyclic epoxy resin and the aliphatic epoxy resin is (0.5-5):1, the alicyclic epoxy resin can be 2-10 parts and the aliphatic epoxy resin can be 2-10 parts by weight, so that the alicyclic epoxy resin and the aliphatic epoxy resin can give full play to their respective performance advantages, and work synergistically with 0.5-5 parts of toughening agent, 0.05-1 parts of curing agent and 0.1-10 parts of conductive filler, so that the thermosetting electrolyte-resistant adhesive has excellent conductivity, adhesion and reliability after curing, lower volume resistivity and stronger solvent resistance, so as to achieve reliable bonding of the pole piece and the pole ear, and effectively improve the safety and energy density of the battery.

[0051] It should be understood that, when the toughening agent is less than 0.5 parts by weight, the synergistic effect with the aliphatic epoxy resin is weak, the stress relief effect on the thermosetting electrolyte-resistant adhesive during the curing process is poor, and the toughness of the thermosetting electrolyte-resistant adhesive after curing is weak, and the electrolyte resistance performance is limited; when the toughening agent is greater than 5 parts, it will inhibit the curing reaction process of the alicyclic epoxy resin and the aliphatic epoxy resin, and the ideal stress relief effect cannot be achieved, and the thermosetting electrolyte-resistant adhesive is too soft after curing, and the electrolyte resistance performance deteriorates.

[0052] Secondly, the curing agent is mainly used to initiate the ring-opening polymerization of the epoxy groups in the alicyclic epoxy resin and the aliphatic epoxy resin under heating, so as to cause the alicyclic epoxy resin to undergo a cross-linking reaction, and realize the curing of the alicyclic epoxy resin and the aliphatic epoxy resin. In terms of weight, if the weight of the curing agent is less than 0.05 parts, the resin system is prone to incomplete curing, the reaction rate is too slow, resulting in the presence of unreacted epoxy groups or insufficient cross-linking degree in the cured product, thereby affecting the bonding stability and reliability; when the weight of the curing agent is greater than 5 parts, it is easy to cause the curing reaction rate to be too fast, and the stress relaxation during the curing process of the thermosetting electrolyte-resistant adhesive is insufficient, resulting in poor bonding performance and reliability of the cured product.

[0053] In addition, when the conductive filler is less than 0.1 parts, the volume resistivity of the thermosetting electrolyte-resistant adhesive after curing is relatively high. When the thermosetting electrolyte-resistant adhesive is used for bonding pole pieces and pole ears, the energy density of the battery is limited; when the conductive filler is greater than 10 parts, it is easy to form uneven distribution in the cured product to form agglomeration or precipitation, which affects the stability and reliability of the cured product during conductivity; therefore, the conductive filler is designed to be 0.1-10 parts, and based on the adhesive layer formed by the cured product, the pole piece and the pole ear can achieve vertical conductivity based on the adhesive layer interface, so as to improve the stability and reliability of the pole piece and the pole ear during conductivity, and ensure that the energy density of the battery is not limited.

[0054] In some embodiments, the alicyclic epoxy resin and / or the aliphatic epoxy resin is a liquid resin or a solid resin; the alicyclic epoxy resin and the aliphatic epoxy resin can be selected as a liquid resin or a solid resin respectively, both of which can make the thermosetting electrolyte-resistant adhesive have a high initial adhesion during the curing process, low volume resistivity after curing, and strong solvent resistance, and the cured product can maintain excellent adhesion and reliability.

[0055] In some embodiments, when the alicyclic epoxy resin is a liquid resin, the liquid viscosity is 20-6000 cP, and has suitable fluidity to facilitate the mixing of various components in the preparation process of the thermosetting electrolyte-resistant adhesive.

[0056] In some embodiments, when the aliphatic epoxy resin is a liquid resin, the liquid viscosity is 50-100000 cP, so as to prolong the reaction time of the aliphatic epoxy resin when it is cured after the alicyclic epoxy resin is fully cured, so as to fully relieve the stress generated by the curing of the alicyclic epoxy resin.

[0057] In some embodiments, the epoxy equivalent of the alicyclic epoxy resin is 70-250 EEW (g / mol), and the epoxy equivalent of the aliphatic epoxy resin is 90-500 EEW (g / mol). When the epoxy equivalents of the alicyclic epoxy resin and the aliphatic epoxy resin are respectively within the above ranges, the epoxy equivalent of the alicyclic epoxy resin can be designed to be lower than the epoxy equivalent of the aliphatic epoxy resin, so as to facilitate the first curing of the alicyclic epoxy resin and the post-curing of the epoxy equivalent of the aliphatic epoxy resin.

[0058] In some embodiments, the functionality of the alicyclic epoxy resin and / or the aliphatic epoxy resin is 2-4, so that the alicyclic epoxy resin and the aliphatic epoxy resin have a suitable crosslinking density after curing, so that the cured product of the thermosetting electrolyte-resistant adhesive can maintain excellent adhesion and reliability.

[0059] In some embodiments, the alicyclic epoxy resin includes 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexylmethyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, poly[(2-oxiranyl)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether (3:1), 3,4-epoxycyclohexylmethyl methacrylate, vinylcyclohexene dioxide, 3,4-epoxycyclohexyl methacrylate, dipentene dioxide, 1,2 - at least one of epoxy-4-vinylcyclohexane, tetrahydroindole diepoxide, 2-(3,4-epoxycyclohexyl)-5,5-spiro(3,4-epoxycyclohexyl)-1,3-dioxane homopolymer, (3,4,3',4'-diepoxy)bicyclohexane, 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylate) or dicyclopentadiene diepoxide; for example, the alicyclic epoxy resin may be CELLOXIDE produced by Daicel or Tytel. 2021P, CELLOXIDE 8010, CELLOXIDE 2081, CELLOXIDE 2000, EHPE 3150, EHPE3150CE, EPOLEAD GT401, etc.; the above substances, as the alicyclic epoxy resins in the embodiments of the present application, can synergize with the aliphatic epoxy resin, the curing agent, the toughening agent and the conductive filler to give the cured product of the thermosetting electrolyte-resistant adhesive excellent bonding performance, thermal stability and solvent resistance.

[0060] In some embodiments, the aliphatic epoxy resin includes at least one of a bisphenol A epoxy resin, a bisphenol F epoxy resin, a biphenyl epoxy resin with a difunctional structure, an aminophenol epoxy resin, and a naphthol epoxy resin with a trifunctional structure; the above substances, as the aliphatic epoxy resins in the embodiments of the present application, can continue to slowly cure after the alicyclic epoxy resin has reacted completely, and synergize with the toughening effect of the toughening agent to jointly alleviate the stress generated during the curing process of the alicyclic epoxy resin.

[0061] In some embodiments, the toughening agent includes at least one of polybutadiene rubber or nitrile rubber; the addition of polybutadiene rubber or nitrile rubber can effectively reduce the stress during the curing process of the thermosetting electrolyte-resistant adhesive, improve the hot and cold shock resistance of the cured product, and have a good effect on electrolyte resistance. The above substances, as toughening agents in the embodiments of the present application, can improve the electrolyte resistance of the thermosetting electrolyte-resistant adhesive and at the same time play a toughening role.

[0062] In some embodiments, the toughening agent specifically includes at least one of epoxidized polybutadiene or core-shell rubber epoxy dispersion (the core part is polybutadiene or nitrile rubber, and the shell part is alicyclic epoxy resin); epoxidized polybutadiene or core-shell rubber epoxy dispersion as polybutadiene rubber or nitrile rubber, are liquid rubbers, specifically such as Japan KANEKA's MX series of core-shell rubbers, including NBR (nitrile rubber) and CTBN (carboxyl-terminated liquid nitrile rubber) core-shell rubber dispersions, Cray Valley RICON series POLYBD resins, etc.; polybutadiene rubber or nitrile rubber can also use solid rubbers such as core-shell rubber powder.

[0063] In some embodiments, the curing agent is a cationic thermal curing agent, including at least one of hexafluoroantimonate, blocked diphenyliodonium antimonate, blocked diphenyliodonium phosphate, blocked triarylsulfonium hexafluorophosphate, ammonium blocked Lewis acid salt and pentafluorophenyl boric acid sulfonium salt; for example, the curing agent can be SI-60L, SI-80L, SI-100L of Sanxin Chemical or CXC-1612 of King Industries; the above substances are all cationic thermal curing agents, and the cations generated by the cationic thermal curing agent when heated can be added to the epoxy group, causing the ring-opening polymerization of the epoxy group, thereby causing alicyclic epoxy resins to undergo cross-linking reactions to achieve a curing effect.

[0064] In some embodiments, the conductive filler includes at least one of superconducting carbon, graphite, hard carbon, silver powder, silver-coated copper powder, silver-coated nickel powder, nickel powder, silver-coated glass, silver-coated graphite, tin-silver-copper powder or carbon nanotubes. All of the above substances have good electrical conductivity. As conductive fillers, they can give the cured product of the thermosetting electrolyte-resistant adhesive excellent conductivity to meet the conductivity requirements when connecting the lithium battery pole piece and the pole ear.

[0065] In some embodiments, the particle size of the conductive filler is in the range of 0.2-100 μm, so as to facilitate uniform dispersion of the conductive filler in the cured product of the thermosetting electrolyte-resistant adhesive.

[0066] In order to improve the ease of operation of the thermosetting electrolyte-resistant adhesive when bonding the tabs and pole pieces, in some embodiments, the raw materials of the thermosetting electrolyte-resistant adhesive also include, by weight: diluent: 0.01-5 parts; for example, by weight, the diluent can be 0.01 parts, 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts or any parts by weight within the range of 0.01-5 parts; 0.01-5 parts of diluent can adjust the viscosity of the thermosetting electrolyte-resistant adhesive to an appropriate state, so that when the thermosetting electrolyte-resistant adhesive is used for bonding the tabs and pole pieces, continuous spraying construction can be adopted to improve production efficiency.

[0067] In some embodiments, the diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent or an oxidized cyclobutane diluent, such as OXT-212, OXT-221, OXT-213, OXT-101, etc. produced by East Asia Synthetics, ED509S produced by ADEKA, E10P produced by Momentive, EX201 produced by Nagase, GMA produced by Mitsubishi, etc.; the above substances as diluents can reduce the viscosity of the thermosetting electrolyte-resistant adhesive and have little effect on the performance of the formed cured product.

[0068] In some embodiments, the raw materials of the thermosetting electrolyte-resistant adhesive further include, by weight: epoxy-modified PP prepolymer: 1-10 parts.

[0069] It should be noted that the epoxy-modified PP prepolymer can be obtained by grafting epoxy groups on the molecular chain of hydroxy-modified PP or maleic anhydride-grafted PP, and the grafted epoxy groups are aliphatic epoxy groups, so that the epoxy-modified PP prepolymer has a lower polarity, which is conducive to improving the electrolyte resistance. Under the action of the curing agent, the epoxy-modified PP prepolymer participates in the curing reaction of the thermosetting electrolyte-resistant adhesive, which significantly improves the electrolyte resistance of the cured product of the thermosetting electrolyte-resistant adhesive. Therefore, by introducing 1-10 parts of epoxy-modified PP prepolymer into the thermosetting electrolyte-resistant adhesive component, the epoxy-modified PP prepolymer can replace part of the toughening agent and aliphatic epoxy resin, and further enhance the electrolyte resistance of the cured product.

[0070] In some embodiments, the molecular weight of the epoxy-modified PP prepolymer is 1000-100000 to ensure good dispersibility and reactivity in the system.

[0071] Another embodiment of the present application provides a method for preparing a thermosetting electrolyte-resistant adhesive, comprising uniformly mixing alicyclic epoxy resin, aliphatic epoxy resin, a curing agent, a toughening agent and a conductive filler in a predetermined proportion to obtain a thermosetting electrolyte-resistant adhesive.

[0072] Furthermore, the preparation method of the thermosetting electrolyte resistant adhesive specifically comprises the following steps:

[0073] The first mixing stage: uniformly mixing the alicyclic epoxy resin, the aliphatic epoxy resin and the toughening agent, or uniformly mixing the alicyclic epoxy resin, the aliphatic epoxy resin, the toughening agent and the epoxy-modified PP prepolymer to obtain a first mixed product;

[0074] The second mixing stage: adding the curing agent to the first mixed product and mixing evenly to obtain a second mixed product;

[0075] The third mixing stage: uniformly dispersing the conductive filler in the second mixed product to obtain a thermosetting electrolyte-resistant adhesive.

[0076] In some embodiments, the third mixing stage also includes adding a predetermined proportion of diluent to the thermosetting electrolyte-resistant adhesive and mixing it evenly to reduce the viscosity of the thermosetting electrolyte-resistant adhesive and facilitate the construction when using the thermosetting electrolyte-resistant adhesive for bonding.

[0077] In some embodiments, dispersing the conductive filler in the second mixed product includes a first dispersing stage and a second dispersing stage performed sequentially, so as to facilitate uniform dispersion of the conductive filler.

[0078] In some embodiments, the first mixing stage, the second mixing stage and the third mixing stage are all carried out under stirring conditions at room temperature to enable the components to be fully mixed.

[0079] In some embodiments, in the first mixing stage or the second mixing stage: the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min, so as to facilitate mixing of the components in the first mixed product or the second mixed product.

[0080] In some embodiments, the stirring speed of the mixing container in the first dispersing stage is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min, so as to facilitate the conductive filler to be fully mixed into the second mixed product.

[0081] In some embodiments, the stirring speed of the mixing container in the second dispersion stage is controlled within the range of 30-100 rpm, the dispersion speed of the mixing container is controlled within the range of 600-1000 rpm, the stirring time is controlled within the range of 10-30 min, and the mixing temperature is controlled below 30° C., so as to facilitate uniform dispersion of the conductive filler.

[0082] It should be noted that the third mixing stage uses a double planetary stirring kettle as a mixing container to facilitate accurate control of the stirring speed of the first dispersing stage and the second dispersing stage.

[0083] In some embodiments, adding a predetermined proportion of diluent to the thermosetting electrolyte-resistant adhesive includes a mixing stage and a vacuum degassing stage performed sequentially. During the mixing stage and the vacuum degassing stage, the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min, respectively, so as to reduce the viscosity of the thermosetting electrolyte-resistant adhesive and avoid bubbles remaining in the thermosetting electrolyte-resistant adhesive.

[0084] In some embodiments, when the thermosetting electrolyte-resistant adhesive introduces an epoxy-modified PP prepolymer component, as an example, the epoxy-modified PP prepolymer can be prepared by prepolymerizing an epoxy-active diluent and maleic anhydride grafted polypropylene (MAH-g-PP) as raw materials under the action of a catalyst, specifically comprising the following steps: weighing MAH-g-PP and adding it into a reaction container, heating it to 150°C for melting; weighing the epoxy-active diluent and adding it into the reaction container, evacuating the container, and controlling the stirring speed at 200-500rpm to uniformly mix the reaction system; after uniform mixing, adding a catalyst into the reaction container, raising the temperature to 170°C, ensuring that the temperature in the reaction container is 160°C±5°C, reacting for 1-3h, and the entire reaction process is carried out in a vacuum environment; after the reaction is complete, the material is discharged and cooled to obtain an epoxy-modified PP prepolymer.

[0085] In the preparation process of the epoxy-modified PP prepolymer, the epoxy active diluent includes at least one of polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, and hexanediol diglycidyl ether; the molecular weight of maleic anhydride grafted polypropylene is 1000-50000, such as Dow's GA1000R, Mitsui's ADMER series, etc.; the catalyst can be at least one of triphenylphosphine, N,N-dimethylaniline, triethylamine, tetramethylammonium bromide or tetraethylammonium bromide. In the preparation process of the epoxy-modified PP prepolymer, the mass ratio of epoxy active diluent to maleic anhydride grafted polypropylene can be (8-10): 1, and the catalyst accounts for 1%-2% of the total mass percentage.

[0086] Another embodiment of the present application provides the above-mentioned thermosetting electrolyte-resistant adhesive, and its application in bonding lithium battery pole pieces and tabs.

[0087] When the thermosetting electrolyte-resistant adhesive in the present embodiment is used for bonding lithium battery pole pieces and tabs, it has excellent bonding strength to metal aluminum, metal nickel, and metal copper, and has high shear strength. It can complete preliminary curing or full curing within 1 to 5 seconds at 180 to 250°C, and can be fully cured within 4 hours at 85 to 110°C. Experimental verification shows that the cured product has low dissolution rate and swelling rate in an electrolyte environment, and can achieve stable and reliable bonding of lithium battery pole pieces and tabs. The cured product can still maintain high bonding stability under long-term electrolyte erosion, and compared with the method of connecting the tabs and pole pieces by welding, the safety and energy density of the battery are effectively improved.

[0088] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0089] Example 1

[0090] The first mixing stage: 6 parts of alicyclic epoxy resin, 2 parts of aliphatic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is carried out for 15 minutes to obtain a first mixed product;

[0091] Second mixing stage: add 0.2 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0092] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, and continue stirring for 20 minutes to obtain a thermosetting electrolyte-resistant adhesive A1.

[0093] Example 2

[0094] The first mixing stage: 4 parts of alicyclic epoxy resin, 2 parts of aliphatic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is carried out for 15 minutes to obtain a first mixed product;

[0095] Second mixing stage: add 0.3 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0096] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50rpm, continue stirring for 20 minutes to obtain a thermosetting electrolyte-resistant adhesive; add 2 parts of diluent to the thermosetting electrolyte-resistant adhesive, control the stirring speed to 30rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting electrolyte-resistant adhesive A2.

[0097] Example 3

[0098] The first mixing stage: 2 parts of alicyclic epoxy resin, 4 parts of aliphatic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;

[0099] Second mixing stage: add 0.5 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0100] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50rpm, continue stirring for 20 minutes to obtain a thermosetting electrolyte-resistant adhesive; add 2 parts of diluent to the thermosetting electrolyte-resistant adhesive, control the stirring speed to 30rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting electrolyte-resistant adhesive A3.

[0101] Example 4

[0102] The first mixing stage: 3 parts of alicyclic epoxy resin, 3 parts of aliphatic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;

[0103] Second mixing stage: add 0.3 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0104] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50rpm, continue stirring for 20 minutes to obtain a thermosetting electrolyte-resistant adhesive; add 2 parts of diluent to the thermosetting electrolyte-resistant adhesive, control the stirring speed to 30rpm, stir for 10 minutes, and continue stirring for 20 minutes in a vacuum environment, then discharge the material to obtain a thermosetting electrolyte-resistant adhesive A4.

[0105] Example 5

[0106] First mixing stage: 3 parts of alicyclic epoxy resin, 2 parts of aliphatic epoxy resin, 3 parts of epoxy-modified PP prepolymer and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is carried out for 15 minutes to obtain a first mixed product;

[0107] Second mixing stage: add 0.3 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0108] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes, and obtain a thermosetting electrolyte-resistant adhesive A5.

[0109] Example 6

[0110] The first mixing stage: 8 parts of alicyclic epoxy resin, 2 parts of aliphatic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;

[0111] Second mixing stage: add 0.15 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0112] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, and continue stirring for 20 minutes to obtain a thermosetting electrolyte-resistant adhesive A6.

[0113] Comparative Example 1

[0114] First mixing stage: 8 parts of aliphatic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;

[0115] Second mixing stage: add 0.3 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0116] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes, and obtain comparative adhesive B1.

[0117] Comparative Example 2

[0118] First mixing stage: 8 parts of alicyclic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;

[0119] Second mixing stage: add 0.3 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0120] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes, and obtain comparative adhesive B2.

[0121] Comparative Example 3

[0122] The first mixing stage: 2 parts of alicyclic epoxy resin, 6 parts of alicyclic epoxy resin and 2 parts of toughening agent are added into a double planetary stirring reactor for mixing, the stirring speed is controlled at 30 rpm, and the stirring is performed for 15 minutes to obtain a first mixed product;

[0123] Second mixing stage: add 0.3 parts of curing agent to the first mixed product and mix, maintain the original stirring speed and continue stirring for 15 minutes to obtain a second mixed product;

[0124] The third mixing stage: add 0.5 parts of conductive filler to the second mixed product, control the stirring speed to 30 rpm, continue stirring for 10 minutes, then turn on the high-speed dispersion disk of the double planetary stirring reactor, control the dispersion speed to 800 rpm, water-cooled and temperature controlled below 30°C, increase the stirring speed to 50 rpm, continue stirring for 20 minutes, and obtain comparative adhesive B3.

[0125] Comparative Example 4

[0126] The preparation method is the same as that of Example 1, except that the toughening agent is 6 parts, and finally a comparative example adhesive B4 is obtained.

[0127] Comparative Example 5

[0128] The preparation method is the same as that of Example 1, except that no toughening agent is used, and finally a comparative example adhesive B5 is obtained.

[0129] Comparative Example 6

[0130] Hot melt glue B6 is used, which comes from DZ230326B of Tuodi Chemical.

[0131] It should be noted that in the above embodiments and comparative examples, the alicyclic epoxy resin is commercially available Desail EHPE3150CE, the aliphatic epoxy resin is commercially available DIC 830S, the toughening agent is commercially available Crayville Polybd 605E, the diluent is commercially available Curalite OxPlus, the curing agent is commercially available King industries CXC-1612, and the conductive filler is commercially available Cabot VXC-72.

[0132] In addition, in the above embodiments and comparative examples, the preparation process of epoxy-modified PP prepolymer is as follows: 9 parts of maleic anhydride grafted polypropylene are weighed and added to the reaction container, and the temperature is raised to 150°C for melting; 1 part of polypropylene glycol diglycidyl ether is weighed and added to the reaction container, vacuumed, and the stirring speed is controlled at 200-500rpm to make the reaction system uniformly mixed; after uniform mixing, 0.5 parts of triphenylphosphine are added to the reaction container, the temperature is raised to 170°C, and the temperature in the reaction container is ensured to be 160°C ± 5°C, and the reaction is carried out for 2h, and the reaction process is carried out in a vacuum environment throughout; after the reaction is complete, the material is discharged and cooled to obtain epoxy-modified PP prepolymer. Among them, the maleic anhydride grafted polypropylene is Dow's GA1000R.

[0133] The raw material component information of the adhesives A1 to B5 obtained in the above embodiments and comparative examples is shown in Table 1 below, in parts by weight:

[0134] Table 1. Statistical table of raw material components of examples and comparative examples

[0135]

[0136] In order to verify the performance of the thermosetting adhesives A1 to B5 and the hot melt adhesive B6 prepared in each embodiment and comparative example, the following performance tests were performed on A1 to B6 respectively:

[0137] (1) Curing time test:

[0138] Drop thermosetting adhesives A1 to B5 between two metal sheets (copper foil) respectively, and then heat press at 180°C, with the heat pressing time increasing by 1s in steps starting from 1s. After heat pressing, take out the two metal sheets and tear them apart. If the glue inside is not cured by visual judgment, re-sample and enter the subsequent time period test. If the glue inside is cured by visual judgment, take part of the cured product for DSC test to observe whether there will be an exothermic peak. If there is an exothermic peak, re-sample and enter the subsequent time period test. If there is no exothermic peak, the corresponding heat pressing time is the 180°C heat pressing curing time. The curing time of hot melt adhesive B6 is recorded as NA.

[0139] (2) Peel strength test:

[0140] 1) Sample preparation: With copper foil as the substrate, the thermosetting adhesives A1 to B5 and the hot melt adhesive B6 prepared in each embodiment and comparative example were respectively scraped on different substrates with a scraper, and cured to form a film with a thickness of 20 μm (i.e., a cured product film), which was then cut into a size of 20 mm×100 mm to obtain a sample;

[0141] 2) Peel strength test before soaking: fix the substrate of the sample on the back plate, peel the film of the sample at 90°, test the 90° peel force, and the peeling speed is 50 mm / min. After testing 3 samples in each embodiment and comparative example, take the average value to obtain the peel strength before soaking.

[0142] 3) Post-immersion peel strength test: The sample was placed in an electrolyte, sealed, and placed in an 85°C oven for 24 hours, then taken out and tested for 90° peel strength; the peeling speed was 50 mm / min, and 3 samples were tested for each embodiment and comparative example, and the average value was taken to obtain the post-immersion peel strength.

[0143] (3) Dissolution rate and swelling rate test:

[0144] 1) Dissolution rate test: Take 1.4±0.1g of the thermosetting adhesives A1~B5 and the hot melt adhesive B6 prepared in each embodiment and comparative example, record the mass as M1, soak them in 7±0.5g of electrolyte, record the mass as M2, then seal them with a syringe bottle, put them in an oven at 85℃, and after aging for 24 hours, take 20±5mg of the clear liquid, heat it to 300℃ at a rate of 10℃ / min using a thermogravimetric analyzer (TGA), read the weight percentage of the residual material, record it as A, and calculate the dissolution rate according to the formula A×M2 / M1.

[0145] 2) Swelling rate test: Take 2±0.1g of adhesives A1~B5 and hot-melt glue B6 prepared in each embodiment and comparative example, record the mass as M1, soak them in 50g electrolyte, put them in an 85℃ oven, age them for 24 hours, take out the glue block, wipe off the electrolyte on its surface, weigh it to get M2, and calculate the swelling rate according to the formula (M2-M1)×100% / M1.

[0146] (4) Contact resistance test:

[0147] Use the same amount of A1 to B6 to bond the tabs and copper foil to make a sample, and perform hot pressing (the hot pressing time is greater than the curing time, and the B6 sample does not need hot pressing). After hot pressing, take out the sample and connect the two probes of the resistor to the copper foil and the tab respectively. Read the value of the resistor, which is the contact resistance of the glue. Soak the hot-pressed sample in electrolyte, place it in an 85℃ oven, age it for 24 hours, take it out and wipe off the electrolyte on its surface, and then test it using the same method to obtain the contact resistance of the glue at 85℃ / 24h. If the tabs and copper foil fall off after soaking, the contact resistance after soaking is recorded as NG.

[0148] The test results of the thermosetting adhesives A1 to B5 and the hot melt adhesive B6 in the embodiments and comparative examples are summarized in Table 2 below.

[0149] Table 2. Statistical table of performance test data of adhesives in embodiments and comparative examples

[0150]

[0151] The advantages of the embodiments of the present application are analyzed in combination with Table 1 and Table 2.

[0152] The thermosetting electrolyte-resistant adhesives A1 to A6 obtained in Examples 1 to 6 are mainly made of alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler as raw materials; wherein the mass ratio of alicyclic epoxy resin to aliphatic epoxy resin is in the range of (0.5-5):1. Compared with Comparative Examples 1 to 6, preliminary curing or complete curing can be achieved within 1 to 5 seconds at 180°C, and the pre-soak peel strength and pre-soak peel strength can be maintained at a high level. The thermosetting electrolyte-resistant adhesives A1 to A6 obtained in each embodiment have high bonding strength and stability. The dissolution rate of the cured product at 85°C / 24h in the electrolyte environment is not higher than 0.7%, and the swelling rate at 85°C / 24h is not higher than 1.2%. The cured product can still maintain a high bonding stability under long-term electrolyte erosion, and can maintain a low contact resistance at room temperature and 85°C / 24h, with excellent conductive properties.

[0153] Specifically, compared with Example 1, Comparative Example 1 has a comparative example adhesive B1 that does not contain alicyclic epoxy resin, resulting in a long curing time, weak electrolyte resistance, and a large swelling rate and dissolution rate.

[0154] Comparative Example 2 Compared with Example 1, the comparative example adhesive B2 does not contain aliphatic epoxy resin, has a lower peel strength before soaking, a weaker initial bonding force, and a higher contact resistance.

[0155] Comparative Example 3 Compared with Example 1, the mass ratio of the alicyclic epoxy resin to the aliphatic epoxy resin in the comparative example adhesive B3 is not within the range of (0.5-5):1, the curing time is too long, and the electrolyte resistance is weak.

[0156] Comparative Example 4 Compared with Example 1, the dosage of the toughening agent in the comparative adhesive B4 is too high, the curing time is long, the electrolyte resistance is weak, the swelling rate and dissolution rate are large, and the contact resistance is high.

[0157] Comparative Example 5 Compared with Example 1, no toughening agent was used in the comparative adhesive B5, the peeling strength before soaking was low, and the initial bonding force was weak.

[0158] Comparative Example 6 uses hot melt glue B6. Compared with the embodiments, the dissolution rate and swelling rate at 85°C / 24h are too high, which is not conducive to the bonding of lithium battery pole pieces and pole ears, and cannot be cured quickly at high temperature.

[0159] It is worth noting that the raw material design of the thermosetting electrolyte-resistant adhesive A5 of Example 5 contains 3 parts of epoxy-modified PP prepolymer, and the dissolution rate and swelling rate of the cured product at 85°C / 24h are lower than those of other examples, which can significantly improve the electrolyte resistance of the cured product.

[0160] At this point, the embodiments of the present application design the components of the thermosetting electrolyte-resistant adhesive so that the thermosetting electrolyte-resistant adhesive has excellent bonding properties, conductivity and electrolyte resistance after thermal curing. When used in the lithium battery production process, the pole pieces and pole ears can be directly bonded with the thermosetting electrolyte-resistant adhesive to replace the traditional technology of welding to connect the pole pieces and pole ears, thereby avoiding the formation of burrs, welding slag, welding points and metal particles during welding, and there is no need to use protective tape to cover the pole pieces, thereby effectively improving the safety and energy density of the battery.

[0161] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A thermosetting electrolyte-resistant adhesive, characterized in that: The thermosetting electrolyte-resistant adhesive is mainly made of alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler as raw materials; Wherein, the mass ratio of the alicyclic epoxy resin to the aliphatic epoxy resin is (0.5-5):

1.

2. The thermosetting electrolyte-resistant adhesive according to claim 1, characterized in that: In parts by weight, the thermosetting electrolyte-resistant adhesive comprises: Alicyclic epoxy resin: 2-10 parts; aliphatic epoxy resin: 2-10 parts; toughening agent: 0.5-5 parts; curing agent: 0.05-1 parts; conductive filler: 0.1-10 parts.

3. The thermosetting electrolyte-resistant adhesive according to claim 1, characterized in that: The alicyclic epoxy resin and / or the aliphatic epoxy resin is a liquid resin or a solid resin; Optionally, when the alicyclic epoxy resin is a liquid resin, the liquid viscosity is 20-6000 cP; Optionally, when the aliphatic epoxy resin is a liquid resin, the liquid viscosity is 50-100000 cP; Optionally, the cycloaliphatic epoxy resin has an epoxide equivalent weight of 70-250 EEW (g / mol); Optionally, the epoxy equivalent weight of the aliphatic epoxy resin is 90-500 EEW (g / mol); Optionally, the functionality of the alicyclic epoxy resin and / or the aliphatic epoxy resin is 2-4.

4. The thermosetting electrolyte-resistant adhesive according to any one of claims 1 to 3, characterized in that: At least one of the following AE conditions is met: A. The alicyclic epoxy resin includes 3,4-epoxycyclohexylcarboxylic acid-3',4'-epoxycyclohexyl methyl ester, bis((3,4-epoxycyclohexyl)methyl)adipate, poly[(2-epoxyethylene)-1,2-cyclohexanediol]2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol ether (3:1), 3,4-epoxycyclohexyl methyl methacrylate, vinyl cyclohexene dioxide, 3,4-epoxycyclohexyl At least one of methacrylate, dipentylene dioxide, 1,2-epoxy-4-vinylcyclohexane, tetrahydroindole diepoxide, 2-(3,4-epoxycyclohexyl)-5,5-spiro(3,4-epoxycyclohexyl)-1,3-dioxane homopolymer, (3,4,3',4'-diepoxy)bicyclohexane, 1,4-cyclohexanedimethanol bis(3,4-epoxycyclohexanecarboxylate) or dicyclopentadiene diepoxide; B. The aliphatic epoxy resin includes at least one of a bisphenol A epoxy resin, a bisphenol F epoxy resin, a biphenyl epoxy resin, a trifunctional aminophenol epoxy resin, and a naphthol epoxy resin; C. The toughening agent includes at least one of polybutadiene rubber or nitrile rubber; D. The curing agent is a cationic thermal curing agent, including at least one of hexafluoroantimonate, blocked diphenyliodonium antimonate, blocked diphenyliodonium phosphate, blocked triarylsulfonium hexafluorophosphate, ammonium blocked Lewis acid salt and pentafluorophenyl boric acid sulfonium salt; E. The conductive filler includes at least one of superconducting carbon, graphite, hard carbon, silver powder, silver-coated copper powder, silver-coated nickel powder, nickel powder, silver-coated glass, silver-coated graphite, tin-silver-copper powder or carbon nanotubes.

5. The thermosetting electrolyte-resistant adhesive according to claim 4, characterized in that: The toughening agent specifically includes at least one of epoxidized polybutadiene or core-shell rubber epoxy dispersion; Optionally, the particle size of the conductive filler is in the range of 0.2-100 μm.

6. The thermosetting electrolyte-resistant adhesive according to claim 1, characterized in that: In parts by weight, the raw materials of the thermosetting electrolyte-resistant adhesive further include: diluent: 0.01-5 parts; Optionally, the diluent includes at least one of a glycidyl ether diluent, a glycidyl ester diluent or a cyclobutane oxide diluent; Optionally, the raw materials of the thermosetting electrolyte-resistant adhesive further include, by weight: epoxy-modified PP prepolymer: 1-10 parts. Optionally, the molecular weight of the epoxy-modified PP prepolymer is 1000-100000.

7. A method for preparing the thermosetting electrolyte-resistant adhesive according to any one of claims 1 to 6, characterized in that: The process comprises uniformly mixing alicyclic epoxy resin, aliphatic epoxy resin, curing agent, toughening agent and conductive filler in a predetermined proportion to obtain a thermosetting electrolyte-resistant adhesive.

8. The method for preparing the thermosetting electrolyte-resistant adhesive according to claim 7, characterized in that: The specific steps include: The first mixing stage: uniformly mixing the alicyclic epoxy resin, the aliphatic epoxy resin and the toughening agent, or uniformly mixing the alicyclic epoxy resin, the aliphatic epoxy resin, the toughening agent and the epoxy-modified PP prepolymer to obtain a first mixed product; The second mixing stage: adding the curing agent to the first mixed product and mixing evenly to obtain a second mixed product; The third mixing stage: uniformly dispersing the conductive filler in the second mixed product to obtain a thermosetting electrolyte-resistant adhesive.

9. The method for preparing the thermosetting electrolyte-resistant adhesive according to claim 8, characterized in that: The third mixing stage also includes adding a predetermined proportion of diluent into the thermosetting electrolyte-resistant adhesive and mixing; Optionally, dispersing the conductive filler in the second mixed product includes a first dispersing stage and a second dispersing stage performed sequentially; Optionally, the first mixing stage, the second mixing stage and the third mixing stage are all carried out under stirring conditions; Optionally, in the first mixing stage or the second mixing stage: the stirring speed of the mixing container is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min; Optionally, the stirring speed of the mixing container in the first dispersing stage is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min; Optionally, the stirring speed of the mixing container in the second dispersion stage is controlled within the range of 30-100 rpm, the dispersion speed of the mixing container is controlled within the range of 600-1000 rpm, the stirring time is controlled within the range of 10-30 min, and the mixing temperature is controlled below 30° C.; Optionally, the adding of a predetermined proportion of diluent to the thermosetting electrolyte-resistant adhesive includes a mixing stage and a vacuum degassing stage performed sequentially, and the stirring speed of the mixing container during the mixing stage and the vacuum degassing stage is controlled within the range of 5-60 rpm, and the stirring time is controlled within the range of 10-30 min.

10. The thermosetting electrolyte-resistant adhesive according to any one of claims 1 to 6, wherein the thermosetting electrolyte-resistant adhesive is used in bonding lithium battery pole pieces and tabs.